A study on resource reallocation in regional energy networks based on the adjustment of supply and demand nodes. Issue 1 (1st February 2022) - Zhou, Xichao; Cong, Lin; Li, Na; Zhu, Haifeng
Abstract: In this paper, we propose and analyse a regional energy network resource allocation scheme and optimization model for regions where the number of energy supply nodes grows seasonally, including the optimal division of the energy supply range of each energy supply node based on distance, the optimal path planning scheme of the energy pipeline network connecting energy supply and consumption nodes, and the optimal allocation/reallocation model of regional energy network resources with the objective of optimal operational economy. The proposed scheme for the optimal redistribution of regional energy network resources is used to analyse and study the case area, and a scheme for the division of energy supply nodes in the case area, a scheme for the construction path of energy pipeline network and a planning strategy for the optimal redistribution of energy network resources are developed to verify the feasibility of the method in this paper.